Understanding procedural coding - Bowie, Mary Jo (Delmar Cengage Learning, 2008)
Gain confidence in procedural coding with this comprehensive, hands-on worktext. Practice exercises are provided throughout to help you test yourself as you go, and procedures are illustrated to clarify concepts. When used in conjunction with your CPT manual, this learning resource will help you master procedural coding for all medical specialties. This worktext will allow you to answer questions right in the book, making it both a learning tool and a personalized resource